Measuring calibration factors by imaging a dish of cells expressing different tandem constructs plasmids. Issue 6 (12th February 2021) - Yin, Ao; Sun, Han; Chen, Hongce; Liu, Zhi; Tang, Qiling; Yuan, Ye; Tu, Zhuang; Zhuang, Zhengfei; Chen, Tongsheng
Abstract: Three‐cube Förster resonance energy transfer (FRET) method is the most extensively applied approach for live‐cell FRET quantification. Reliable measurements of calibration factors are crucial for quantitative FRET measurement. We here proposed a modified TA‐G method (termed as mTA‐G) to simultaneously obtain the FRET‐sensitized quenching transition factor ( G ) and extinction coefficients ratio ( γ ) between donor and acceptor. mTA‐G method includes four steps: (1) predetermining the ratio ranges of the sensitized emission of acceptor ( F C ) to the donor excitation and donor channel image ( I DD [ ( DA] )) for all FRET plasmids; (2) culturing the cells which express every FRET plasmid in one dish respectively; (3) distinguishing and marking the cells expressing different FRET plasmids by detecting their F C /I DD ( DA ) values; (4) linearly fitting F C /I AA ( DA ) (acceptor excitation and acceptor channel image) to I DD ( DA )/ I AA ( DA ) for different kinds of cells. We implemented mTA‐G method by imaging tandem constructs cells with different FRET efficiency cultured in one dish on different days, and obtained consistent G and γ values. mTA‐G method not only circumvents switchover of different culture dishes but also keep the constant imaging conditions, exhibiting excellent robustness, and thus will expands the biological applications of quantitative FRET analysis in living cells.